Material selection for Spin-Transfer-Torque Magnetic Random Access Memories: a High-Throughput approach - BOSONI, EMANUELE (Trinity College Dublin. School of Physics. Discipline of Physics, 2020)
A Spin-Transfer-Torque Magnetic Random Access Memory (STT-MRAM) is a complex multilayered structure, whose sensitive element is formed by two ferromagnetic layers sandwiching an insulator, acting as a tunnel barrier. The operational principles of the memory rely on two physical effects: the tunnel magneto-resistance (the total resistance of the device depends on the relative orientation of the magnetization vectors of the two magnetic layers) and the spin-transfer-torque effect (the possibility of inducing magnetization reversal by means of a polarized electric current). The STT-MRAM technology shows promising features for the creation of a new class of memories that combines nonvolatility with access speed close to that of a Dynamic Random Access Memory. At present, the Fe-Co/MgO materials set gives the best performance, but it is not clear whether further improvement will be possible. Fundamental research is needed to lead the design of new efficient junctions. Even though interfaces play a relevant role in this technology, some peculiar material-related features of the various components are essential for the device operation. Looking for these properties would lead to a selection of suitable ferromagnets and insulators to be combined for efficient STT-MRAM structures. This PhD thesis presents a detailed description of the STT-MRAM technology and a strategy for the selection of promising materials is proposed. The main aim is the creation of a database containing material properties of interest for the technology, calculated within the Density Functional Theory (DFT) framework. In order to extend the study to a large set of compounds, the calculations are performed in an high-throughput fashion. An a-posteriori analysis of the information in the database drives the identification of promising candidates for STT-MRAMs. The high-throughput approach is a fairly new methodology in computational material science. In this work, alongside with the scientific investigation, much attention is devoted to the presentation of challenges, benefits and strategies related to the task of performing DFT high-throughput simulations. The main results of the thesis are the identifications of Mn1Ni1 as a good candidate for the role of ferromagnet in an STT-MRAM and the formalization of a theory (and relative implementation) for the calculation of the Complex Band Structure of an insulator that is suitable for the high-throughput methodology. This latter material property is of extreme importance in the STT-MRAM technology, but finds applications also in other situations where the description of quantum tunneling is required.
APPROVED